IMPLEMENTASI PROGRAM BANTUAN LANGSUNG TUNAI DI DESA AGUNG MULYA KECAMATAN TELAGA ANTANG KABUPATEN KOTAWARINGIN TIMUR - Saifudin Saifudin; Farid Nofiard; Amanda Clara Aprilia (Jurnal Caraka Prabu, 2026)
Implementation of the Direct Cash Assistance Program in Agung Mulya Village, Telaga Antang District. This research was conducted with the aim of determining how the direct cash assistance program is implemented in Agung Mulya village. The research method used is a qualitative research approach with a descriptive research type, utilizing Policy Implementation Theory. The results of this study indicate that the implementation of the direct cash assistance program in Agung Mulya village, Telaga Antang sub-district, East Kotawaringin district, is not yet optimal. This can be seen from the less-than-optimal distribution and evaluation processes, where there are still delays in the fund distribution process, and the evaluation process is only carried out once a year, so problems that arise with each fund distribution are not immediately addressed. Meanwhile, the data collection and monitoring processes are already optimal because the data collection is carried out from the bottom up and decisions are made based on the results of discussions. For monitoring, representatives from the village's BPD (Village Consultative Body) are always involved in every activity of the program. Advice to the village government: It is necessary to conduct regular evaluations after the fund distribution process to identify obstacles and find solutions. To the recipients of the aid, it is best to use the aid funds as business capital, for example, for a chip business.